The trinity of good research: distinguishing between research integrity, ethics and governance - Kolstoe, S; Pugh, J (Taylor & Francis, 2023)
The words integrity, ethics and governance are used interchangeably in relation to research. This masks important differences that must be understood when trying to address concerns regarding research culture. While progress has been made in identifying negative aspects of research culture (such as inequalities in hiring/promotion, perverse incentives etc.), and practical issues that lead to research waste (outcome reporting bias, reproducibility etc.), the responsibility for addressing these problems can be unclear due to the complexity of the research environment. One solution is to provide a clearer distinction between the perspectives of “Research Integrity,” “Research Ethics” and “Research Governance.” Here it is proposed that Research Integrity should be understood as focussed on the character of researchers, and consequently the primary responsibility for promoting it lies with researchers themselves. This is a different perspective from Research Ethics, which is focussed on judgments on the ethical acceptability of research, and should primarily be the focus of research ethics committees, often including input from the public as well as the research community. Finally Research Governance is a technical area focussing on legal and policy requirements. Although complementary to research integrity and ethics, Research Governance requires input from expert research support officers with the skills and experience to address technical compliance.